2004
DOI: 10.1177/0085328204044538
|View full text |Cite
|
Sign up to set email alerts
|

Release of Silica, Calcium, Phosphorus, and Fluoride from Glass Ionomer Cement Containing Bioactive Glass

Abstract: The aim of this study was to examine the release of silica (Si), calcium (Ca), phosphorous (P), and fluoride (F) from conventional glass ionomer cement (GI) and resin-modified glass ionomer cement (LCGI), containing different quantities of bioactive glass (BAG). Further aim was to evaluate in vitro biomineralization of dentine. The release of Si increased with the increasing immersion time from the specimens containing BAG, whereas the amount of Ca and P decreased indicating in vitro bioactivity of the materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 12 publications
4
46
1
6
Order By: Relevance
“…The elution of fluoride is a complex process. It is affected by a multitude of intrinsic and environmental factors, such as material composition (which comprises the organic matrix and filler), powder-liquid ratio used in material preparation, mixing method, solubility and porosity of set material mass, surface area of material exposed to the environment, and pH of the environment or storage medium 19,20) . Among the restorative materials, Fuji IX GP, which is a conventional GIC, released significantly more fluoride than the other materials tested.…”
Section: Fluoride Release Before Naf Solution Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The elution of fluoride is a complex process. It is affected by a multitude of intrinsic and environmental factors, such as material composition (which comprises the organic matrix and filler), powder-liquid ratio used in material preparation, mixing method, solubility and porosity of set material mass, surface area of material exposed to the environment, and pH of the environment or storage medium 19,20) . Among the restorative materials, Fuji IX GP, which is a conventional GIC, released significantly more fluoride than the other materials tested.…”
Section: Fluoride Release Before Naf Solution Treatmentmentioning
confidence: 99%
“…Nonetheless, the inclusion of SrF 2 filler particles could result in short-term fluoride release in low amounts. Fluoroaluminosilicate filler particles in GICs are more soluble than SrF 2, thus releasing more fluoride ions 11,20) . Fluoride-releasing dental adhesives released considerable amounts of fluoride ions throughout the 86-day period.…”
Section: Fluoride Release Before Naf Solution Treatmentmentioning
confidence: 99%
“…Alteration in viscosity can interfere severely with the strength of these cements 14 . Bioactive glasses used in the present study have a powder average particle size of 2 µm, which is a lower size than that used in other studies (20 µm) 2,23,24 . If lower sized particles are employed, higher amount of liquid is needed, in order to obtain an adequate cement consistency (Table 2), and the increased amount of liquid to obtain a homogeneous mixture promotes a weaker material 23 .…”
Section: Discussionmentioning
confidence: 73%
“…As bioactive glass particles alone are easily displaced in a clinical environment 9 , a suitable carrier or matrix material is needed to facilitate its use in these settings. Previous studies showed that RMGICs with bioactive glasses yielded positive bioactivity effects 24,23 , a Ca-rich precipitation layer was observed on outer surfaces of the RMGICs, in vitro 24 , in the close vicinity of the restoration-dentin interface and in deeper parts of dentin tubules in vivo 23 . However, these materials exhibited lower mechanical properties than RMGICs 2,23 with similar setting ability 2,12 .…”
Section: Introductionmentioning
confidence: 92%
“…Bu durum materyale eklenen gümüşün veya gümüş florürün, florür iyonlarını bağ-laması ve böylece florür salımını engellemesi ile açıklanabilir. Buna karşılık biyoaktif cam veya kazein fosfopeptit-amorf kalsiyum fosfat içeren cam iyonomerlerin florür salımının geleneksel cam iyonomerlere kıyasla daha yüksek olduğu düşünülmektedir (26,27).…”
Section: A Cam İyonomer Sermet Simanlarunclassified